Utilization of Natural Environment to Improve Early Childhood Creativity - Sofa Muthohar; Aina Yulifaatun Mufida (Universitas Muhammadiyah Ponorogo, 2020)
The natural environment is one of the media that can be used in increasing the creativity of early childhood. The natural environment provides several natural materials that are useful in learning as well as having creative value. This article aimed to find out how to take advantage of this natural environment as a medium in increasing the creativity of early childhood. With this natural environment, early childhood can get to know the natural environment around them. This article used Library Research method, because the data studied were in the form of manuscripts, books that are sourced from libraries. The result of this research is how to take advantage of the natural environment to increase children's creativity by utilizing the natural environment directly and indirectly. There are several driving and inhibiting factors in increasing the creativity of early childhood.